Revitalizing Modern Pesantren Education: A Comparison Of Wahid Hasyim And Yudian Wahyudi Perspective - Zulfatun Ni'mah; Noviandriani Putri; Neni Zakiyah; Tia Nurhaeni; Andi Forisma (At-Tarbiyat, 2023)
Modern era has caused pesantren to decline in presence and appeal, necessitating upgrades in their education system, programs, and curricula to align with contemporary needs. This study examines the concepts of modern pesantren education presented by Wahid Hasyim and Yudian Wahyudi. This type of library research is in the form of comparative and descriptive. The research data collection method is documentation, while the analysis technique used is content and comparative analysis. The analysis reveals that Hasyim and Wahyudi view the pesantren education system as traditional, focusing solely on religious sciences while neglecting experimental sciences. They advocate for dismantling this system by integrating religious knowledge and science. However, they acknowledge the strengths of pesantren in producing scholars proficient in Arabic and Islamic sciences. To revitalize pesantren education, they emphasize integrating religious and scientific knowledge, including general subjects like mathematics and science, and language programs to enhance linguistic skills. They stress the need for pesantren to adapt to the modern world while preserving their identity as centers of classical Islamic scholarship. Wahid Hasyim highlights collaboration among pesantren, the community, and the government, necessitating government support regarding facilities and access. Yudian Wahyudi believes modern pesantren education must apply an inclusive, innovative, and adaptable educational approach to prepare students for social, technical, and cultural changes. Overall, the study highlights the importance of revitalizing pesantren education by integrating religious and scientific knowledge, collaboration, and necessary support to advance Islamic education in the modern era.